Determination of manners of death: an analysis of 3012 postmortem cases - Al-Azad, Md Abdus Samad; Ahmad, Mushtaq; Rahman, Md Zubaidur; Ali, Mohammad; Islam, Sk Md Jaynul (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Forensic Pathologists are often performing autopsies in death investigation. There are five legally-defined manners of death namely natural deaths, accidental deaths, homicidal deaths, suicidal deaths and undetermined deaths. Natural deaths are those that occur from natural causes such as disease or old age rather than from violence or an accident. Objectives: To determine the socio-demographic profile of postmortem cases and to evaluate information regarding manners of deaths as determined by those cases. Methods: This record based cross-sectional study of postmortems performed at the mortuary of the Department of Forensic Medicine; Dhaka Medical College (DMC) was conducted during the period of January 2006 to December 2006. Most of the victims were brought to DMC morgue from south-eastern part of Dhaka district. A total of 3012 autopsies were analyzed during the period. Morgue caters 18 police stations under Dhaka city. Data were collected using a pre-designed schedule from Post mortem registers and reports. All the data were collected in a predefined data collection sheet and necessary statistical analyses were performed by using the computer software SPSS (Statistical Package for Social Science) for window 17.0 and were expressed in frequency and percentage. 19 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Results: A total of 3012 postmortems were studied. Of them 1640 (54.45%) cases were of accidents, 722 (23.97%) cases were of suicide, 542 (17.99%) cases were of homicide, 84 (2.79%) cases were of undetermined and 24 (0.80%) cases were of natural deaths. Most of the postmortem cases were in the age group of 20-40 (54.71%) years, which is the most productive period in life cycle followed by 24.90%, 15.50% and 4.89% in the age group of 0-20 years, 41-60 years and 60 years respectively. Of them 2258 (74.97%) were male and rest 754 (25.03%) cases were female. Conclusion: Accidents, mainly Road Traffic Accident (RTA) and railway accidents, comprise a major manner of death which reduces the most productive period in the life cycle causing serious effects in socio-economic development of the country. RTA can be prevented by specific preventive measures and also by taking personal precautions. Suicide is the second commonest manner of unnatural death flanked by accident and homicide. It is not feasible to draw a concrete conclusion. Homicide is a relatively rare offence than accidents or suicides but it is one of the most notifiable crimes in the country as they are widely publicised by the media due to their severity and visibility. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21820 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013